Is there a Philippine public administration? or better still, for whom is Philippine Public Administration? - Brillantes, Alex B., Jr (Philippine Journal of Public Administration, 2008)
This article traces the evolution of public administration, suggesting that there are only two major phases: traditional and modern. The fields of public administration are discussed taking cognizance of the many other emerging fields going beyond its traditional fields, namely, voluntary sector management and information technology. Selected major ongoing concerns of public administration which include reorganization, decentralization, and corruption in the Philippines are also considered. The article also briefly discusses an example of what is now taken as an emerging illustration of a home-grown governance paradigm, the "Gawad Kalinga" as illustrative of a successful partnership and cooperation between government, business and civil society in the delivery of basic services, which after all is a core concern of modern public administration and good governance. The article ends by raising third-order concerns and challenges as it tries to address the question, "For whom is Philippine public administration?"